The Perspective of Dignified Justice and Human Rights in Business Law Agreements: Towards Ethical and Fair Contracts - Khuan, Hendri; Ishwara, Ade Sathya Sanathana; Paminto, Saptaning Ruju (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The application of the principles of dignified justice and Human Rights (HAM) in business contract law in Indonesia has a very important role in creating economic growth that brings prosperity to all parties. Dignified justice must be carried out by the parties to the agreement so that the objectives of the agreed agreement can be achieved properly. The increasingly complex business contracts often reveal an imbalance in the fulfillment of rights between the parties involved. This situation can result in violations of the principles of justice and human rights, especially for parties whose position is weaker in an agreement, resulting in quite a few business disputes resulting from business agreements that have been made. Therefore, business law has a very important role in safeguarding and protecting the interests of the parties in business agreements. This journal aims to explain the importance of the principle of dignified justice in creating balance between the parties to an agreement, explain the role of human rights as a basis for protecting the fundamental rights of the parties to an agreement, and to identify challenges in implementing the principles of dignified justice and human rights in improving the quality of business agreements in Indonesia